Can we really teach the Generation Z? Opportunities and challenges at secondary level - Erisen, Yavuz; Bavli, Bunyamin (EMERALD GROUP PUBLISHING LTD, 2026)
Purpose- The objective of this study is to explore Generation Z's interpretation of educational practices at the secondary education level. By examining the expectations of Generation Z, this study aims to provide insights for teachers and decision-makers to improve educational and instructional practices. Design/methodology/approach- The specific approach employed in this study is Transcendental Phenomenology (TPh), which focuses on uncovering the perceived experiences, thoughts and evaluations of the Gen Z generation toward formal education. For this study, the maximum variation sampling strategy, which is one of the purposive sampling methods, was utilized. In line with the nature of the design, one-on-one interviews were conducted to collect data. Thematic analysis, a commonly used method for identifying recurring patterns of meaning, was applied to analyze the data. Peer debriefing or analytic triangulation, Data saturation, Triangulation and member checking techniques were operated to support the validity and reliability of the study. Findings- In the light of the data analysis, four themes emerged: expectations from teachers, curricula, school administration and School Counseling Service (SCS). Gen Z expects from teachers to be democratic, to adopt novel teaching approaches and technology, to have affective qualities, to be attentive to arts and sports, to conduct qualified assessment. Gen Z has also expectations regarding the curricula in practice such as functionality, extracurricular activities, and instructional practices. The expectations of the students from school administration include administrative expectations, expectations regarding the learning environment and social expectations. The participants had expectations regarding School Counseling Service (SCS) such as professional guidance, academic guidance and career guidance. Career guidance includes introduction of career paths, academic guidance includes introduction of university programs, exam guidance and teacher training and personal guidance includes accessibility, equity in guidance services, communication and functionality. Research limitations/implications- The research is limited to the volunteers included in the study. In addition, the study includes only senior high school students, 12th graders, representing Gen Z. In addition, the study includes only Gen Z living in a metropolitan city. The methodological limitation of the study is that only one-to-one interview technique was used for data collection. The main reason behind such a choice is that the most appropriate technique for data collection in the phenomenology method is one-on-one interviews in order to explore individual interpretation. Practical implications- The research sheds light on many different points in terms of different applications. One of the results obtained in this context is curriculum. Gen Z criticizes the limitation of the program to only in-school learning and states that extracurricular practices should be included. Findings also presents implications regarding learning environments. There is a growing emphasis by Gen Z on the adoption of green, comfortable and interactive learning spaces. The Generation Z population expects teachers to possess digital competence (DC) and utilize it in their teaching practices. This shows that teachers' teaching competencies need to be upskilled. Social implications- It is crucial for policymakers to support the development of teachers' digital skills and encourage their integration into teaching to enhance instructional productivity, promote innovative learning, increase instructional appeal, foster teamwork, improve communication and facilitate innovative learning. The research reveals that Gen Z is a social phenomenon and needs to be recognized and their learning needs explored. In this context, it is imperative that the preferences and learning needs of Gen Z are considered in the learning environment, content, method-technique and assessment stages, especially in formal education practices. Originality/value- The current research is important both in terms of filling the research gap in the literature and making inferences about the learning preferences of the GEN Z generation. In addition, it raises awareness in terms of the return on educational investments, providing sustainable motivation for learning and school and increasing the quality of learning outcomes. While the study reveals certain implications, further research is required to investigate the competencies of teachers, the effectiveness of teaching materials, instructional practices and designs and learning environments. Future studies should particularly concentrate on the personal preferences, motivation, engagement and learning preferences of Gen Z at the secondary level. Authorities, including teachers, ought to reassess their perspectives and adapt their practices in order to better meet the needs and expectations of Gen Z.
Keywords: Formal education; Expectation; High school; Z generation; Teaching; PHENOMENOLOGY; TECHNOLOGY; Social Sciences - Other Topics